PreservingLiteraryEssence:NarratologyandCinematographic ChoicesinF.ScottFitzgerald'sTheCuriousCaseofBenjamin Button - Benachiba,Chaima; ARIBI,Brahim (Faculty of Letters and Foreign Languages Department of English, 2024)
David Fincher's 2008 film adaptation of F. Scott Fitzgerald's The Curious Case of Benjamin Button is a visually stunning exploration of time, aging, and the human experience. This analysis examines how Fincher's innovative use of digital cinematography complements and enhances the novel's narrative structure. By analyzing the film's camera movements, lighting, and editing techniques, this studydemonstrates howtheadaptation successfully preserves and expands upon the core themes and emotional impact of the original source material. This dissertation employs qualitative questionnaires to examine how the film adaptation shapes audience perceptions and to compare the alternative narrative strategies used in the film and novel. Findings indicate that film adaptation preserves central components of the narrative in the novel, along with many of the details included in it, but plays an important role in providing understanding to the audience as presented on screen and emotional understanding through transitional scenes not present in the literary work. This thesis is intended to enhance our understanding of literary adaptation and the representation of complex narratives into visual form, but also to emphasize the screen image besides the problem of articulation, marking its own set of formal qualities worthy of consideration when analyzing adaptation to screen.